A first-principles study on the structural, thermal and electronic properties of cerium oxides by using different functionals. (20th November 2018) - Sun, Lu; Xiao, Wei; Hao, Xiamin; Meng, Qingling; Zhou, Miao
Abstract: Cerium oxides, such as CeO2 and Ce2 O3, are of great scientific and technological importance for many potential applications. In this work, based on density functional theory (DFT), we performed systematic first-principles calculations to evaluate the performance of different exchange-correlation functionals, including the standard DFT (PBE, PBE sol ), Hubbard-corrected DFT (PBE, PBE sol )+ U, and HSE06 hybrid functionals, in describing the structural, thermal and electronic properties of cerium oxides. We calculated the equilibrium lattice parameters, thermal formation enthalpies, and electronic structures of CeO2 and Ce2 O3, with special attention paid to the gaps, positions and dispersions of O 2 p, Ce 4 f and Ce 5 d bands. Our results suggest that while HSE06 can describe the physical properties of CeO2 with good accuracy with respect to experiment, PBE sol + U with a proper U value gives satisfactory results for Ce2 O3 . Our findings provide valuable information on using different functionals for describing the f -electron localization in cerium oxides, which may also be useful for further explorations of multi-functional materials and electronic devices based on strongly correlated oxide systems.